Applying FSE to enhance customer value by improving store image in different consumer groups. (16th April 2017) - Fu, Hsin-Pin; Chang, Tien-Hsiang; Lin, Arthur; Lin, Sheng-Wei; Chien, Chao-Han
Abstract : Retailers can construct effective marketing strategies to improve their store image and enhance customer value if they understand the nature and the impact of the quantitative data and the qualitative information regarding the factors affecting this image. Most previous studies have used a qualitative or a quantitative method, rather than both. Fuzzy synthetic evaluation (FSE) is a tool for resolving qualitative and quantitative issues. This paper uses FSE in combination with the fuzzy analytic hierarchy process to help companies better understand the quantitative data (the weights of the factors that affect store image) and the qualitative information (the segmentation of consumer groups). By using this quantitative data and qualitative information, retailers can learn pertinent information about each consumer group. Thereby, they can allocate the resources of their enterprises to better improve their store image according to the needs of different customer groups at lower costs and with greater efficiency. The findings and implications found in a case study are discussed.